Classification of prospective students who are eligible to receive KIP Merdeka lecture using the cart algoritma approach / Efori Bu’ulolo … [et al.] - Bu’ulolo, Efori; Fau, Alwin; Ndruru, Eferoni; Waruwu, Fince Tinus; Utomo, Dito Putro (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
To help prospective students who have academic potential but have economic limitations, the government through the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia has programs namely the Smart Indonesia Program (PIP), one of which is KIP Lecture Merdeka. Every year Budi Darma University gets an allocation of KIP Lecture quotas from the Higher Education Service Institute (LLDikti) region I North Sumatra, in the process of determining prospective students who are eligible to receive KIP Lectures Merdeka Budi Darma University often experiences difficulties because the quota is very limited and also prospective students who there are a lot of people who want to go to college with the Merdeka Lecture KIP pathway.